An Analysis of Students’ Ability in Applying Modulation Technique in Translating Collocation “The Lost Symbol” Novel by Dan Brown - Detti Lismayanti; Angga Pratama (Edu-Ling: Journal of English Education and Linguistics, 2019)
The objective of this research was to analyze how students’ ability in applying modulation techniques in translating collocation from the novel “The Lost Symbol” by Dan Brown. The research was a content analysis of descriptive qualitative. There were 25 students taken as respondent, there were represented from each class. The data were collected by using a translation test which was contained six types of collocation. The finding showed that students’ability is dominant in collocation type of adjective and noun because to translate it just simple and the phrase of the word is most familiar in their activities not also in translation subject but other skill language material. In the other hand, the students’ low ability to translate collocation of Verb and expression with a preposition because they could not just use the literal translation but they have to adapt it or changing their point of view and use their cognitive and focus on the context, which makes relevant and coherent. However, overall the average of students ability must be improved it with learning more and lecturer must be able to focus on students’ weakness in applying translation technique, especially on modulation to get the progress by the students’ translation well.